On the Processing Pathway Dependence of Microstructure Evolution During Severe Plastic Deformation: Nickel as a Case Example1. Issue 12 (1st June 2015) - Prokoshkina, Daria; Moros, Anna; Reglitz, Gerrit; Dinda, Guru Prasad; Kuznetsov, Dmitrij D.; Popov, Vladimir V.; Stolbovsky, Alexey V.; Shorohov, Evgeniy; Divinski, Sergiy V.; Wilde, Gerhard
Abstract : Severe plastic deformation (SPD) encompasses various deformation pathways with rather different processing conditions, although seemingly small changes of the initial state of a material or of its impurity content can have a strong impact on the evolution of the microstructure and the associated properties acquired by SPD processing. For analyzing the impact of the processing conditions including the temperature as well as the strain path on the microstructure evolution, nickel has been selected as a model system. Systematic variations of the relevant processing parameters has been facilitated and the resulting materials have been analyzed concerning their microstructures, defects, and also concerning specific kinetic features associated with the grain boundaries after SPD processing. Abstract : Comparison of the results such as the microhardness as function of grain size obtained on Nickel processed along different processing pathways indicates that the extreme states achieved by SPD seem in fact to be achievable also by more conventional processes such as rolling‐based deformation routes that offer access to industrial processing schemes.